EVALUASI TINGKAT PENGETAHUAN MASYARAKAT TERHADAP DAGUSIBU ANTIBIOTIK DI RAWALUMBU KOTA BEKASI - Annisa Aulia Rahmawati; Refdanita Refdanita; Teodhora Teodhora (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2023)
Introduction: Antibiotics are drugs used to treat infections caused by bacteria. In the last few decades, the use of antibiotics has increased remarkably. However, it results in various problems and become a global threat. One of the problems that will occur is the irrational treatment of antibiotics that causes antibiotics resistance. This predicament increases every year because of the lack of public knowledge about the appropriate use of antibiotics. The purpose of this study is to evaluate the public knowledge level on DAGUSIBU of antibiotics in RT 05 RW 11 Bojong Menteng Village, Rawalumbu District, Bekasi City, based on demographic characteristics (gender, age, occupation, and education). Methods: The research design of this study is cross-sectional with the type of descriptive-analytic research. The data are collected from 77 respondents from RT 05 RW 11 follows the inclusion and exclusion criteria. The researcher obtains the primary data from the research instruments in the form of questionnaires that have been tested for validation and reliability. Results: This study on the evaluation of the public knowledge level on DAGUSIBU of antibiotics are according to demographic characteristics, most of the respondents were female (63.6%), pre-elderly (46.7%), secondary education (53.2%), and unemployed (57.1%). Furthermore, based on the evaluation of how to get antibiotics, with sufficient knowledge (37.7%), how to use antibiotics, with insufficient knowledge (35.0%), how to store antibiotics, with proper knowledge (48.0%), and how to dispose of antibiotics, with sufficient knowledge (54.5%). Conclusion: This study reveals that the public knowledge level of RT 05 RW 11 on DAGUSIBU of antibiotics is sufficient.